EDUCATION: REAL AND DUE - Khmel, V. V. (Anthropological Measurements of Philosophical Research, 2012)
The current context of information society is characterized by the growing role and importance of educational technology. To the fore the question of what should be a process of education in the postmodern situation and on the basis of the Bologna concept. The article contains a comparative analysis of educational systems of Germany, Russia and Ukraine.